Repeated PD-1/PD-L1 monoclonal antibody administration induces fatal xenogeneic hypersensitivity reactions in a murine model of breast cancer. (1st February 2016) - Mall, Christine; Sckisel, Gail D.; Proia, David A.; Mirsoian, Annie; Grossenbacher, Steven K.; Pai, Chien-Chun Steven; Chen, Mingyi; Monjazeb, Arta M.; Kelly, Karen; Blazar, Bruce R.; Murphy, William J.
ABSTRACT: Monoclonal antibodies (mAbs) targeting coinhibitory molecules such as PD-1, PD-L1 and CTLA-4 are increasingly used as targets of therapeutic intervention against cancer. While these targets have led to a critical paradigm shift in treatments for cancer, these approaches are also plagued with limitations owing to cancer immune evasion mechanisms and adverse toxicities associated with continuous treatment. It has been difficult to reproduce and develop interventions to these limitations preclinically due to poor reagent efficacy and reagent xenogenecity not seen in human trials. In this study, we investigated adverse effects of repeated administration of PD-1 and PD-L1 mAbs in the murine 4T1 mammary carcinoma model. We observed rapid and fatal hypersensitivity reactions in tumor bearing mice within 30–60 min after 4–5 administrations of PD-L1 or PD-1 mAb but not CTLA-4 antibody treatment. These events occurred only in mice bearing the highly inflammatory 4T1 tumor and did not occur in mice bearing non-inflammatory tumors. We observed that mortality was associated with systemic accumulation of IgG1 antibodies, antibodies specific to the PD-1 mAb, and accumulation of Gr-1 high neutrophils in lungs which have been implicated in the IgG mediated pathway of anaphylaxis. Anti-PD-1 associated toxicities were alleviated when PD-1 blockade was combined with the therapeutic HSP90 inhibitor, ganetespib, which impaired immune responses toward the xenogeneic PD-1 mAb. This study highlights a previously uncharacterized fatal hypersensitivity exacerbated by the PD-1/PD-L1 axis in the broadly used 4T1 tumor model as well as an interesting relationship between this particular class of checkpoint blockade and tumor-dependent immunomodulation.